Pengaruh Tanggung Jawab dan Kemampuan Pegawai terhadap Prestasi Kerja Pegawai Bappeda Kabupaten Banggai - Wahyudin Rahman (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2015)
This study aimed to analyze the influence of the responsibility and the ability of employees on jobs performance of employees either simultaneously or partially on regional development planning agency at Banggai regency. The analytical method used is multiple linear analysis. The results of this study indicate there is positive and signifikanct responsibilities and capabilities of employees on work performance of employees.